Effectiveness Of Cream Formulation Of Carrot Seed Oil As Anti-Aging - Musnaini Musnaini; Silvia Fransisca; William Leslie (International Journal of Health and Pharmaceutical (IJHP), 2023)
Carrot (Daucus carota L.) is a vegetable plant that has many uses for public health services in the world. Fresh carrots contain water, protein, carbohydrates, fat, fiber, ash, anti-cancer nutrients, natural sugars (fructose, sucrose, dextrose, lactose, and maltose), pectin, glutathione, minerals (calcium, phosphorus, iron, potassium, sodium, magnesium, chromium), vitamins (beta carotene, B1, and C) and asparagine. The purpose of this study was to characterize simplicia and carrot seed oil extract, and to determine the antioxidant activity of carrot seed oil extract with formulations of concentrations of 3%, 6% and 9% seeds on the effectiveness of anti-aging Moisture, Evenness, Pore, Spot and Wrinkle. Carrot seed oil can be formulated in a homogeneous cream dosage form with an oil-in-water emulsion type, pH 6.7-7.7; does not cause skin irritation and is stable on storage for 90 days at room temperature. Carrot seed oil cream with a concentration of 9% showed the best anti-aging effectiveness by increasing water content, reducing skin hardness, shrinking pores, reducing blemishes and reducing wrinkles compared to other cream formulas.